PENGARUH REWARD DAN PUNISHMENT TERHADAP MINAT BELAJAR PPKn SISWA KELAS IX MTS. MIFTAHUL HUDA DI DESA SILIKUAN HULU KECAMATAN UKUI KABUPATEN PELALAWAN - KHUSNUL KHOTIMAH; Hambali Hambali; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study motivated students have low learning interest in learning civic education. This is seen when researchers di observations in class some students who enter the classroom when following learning civic education not pay attention to explanations given teachers, they are cool with their respective occupations, delivery of material that is considered less attractive, students are still while doing test questions in learning civic education , late entry into the classroom hours so distrubing the teaching and learning process and when the lesson of studens often premit out, this tends to give teachers reward and punishment to students. Formulations of this problem (1) whether there is a reward effect on interest in learning? (2) whether there is influence punishment to interest in learning? (3) whether there is influence of reward and punishment together towards the interest of learning? The purpose of this study (1) to know the effect of reward on learning interes (2) to know the effect of punishment on interest in learning (3) to know the effect of reward and punishment together on the interest of learning. This research is q quantitative descriptive research. The data were analyzed by using multiple linear regression. There is the effect of reward on interest in learning with tcount 2.571 > ttable 1.71 or 0,019 < 0,05. Ther is a punishment effect on interest in learning with tcount 2.468 > ttable 1.71 or 0,023 < 0,05. There is the effect of reward and punishment together on the interest of learning with equality Y = -8,307 + 1,547(X1) + 1,125(X2). In this research can be seen there is influence of reward and punishment to learning interest of civic education with donation 33,9%.Keyword: Influence, Reward-Punishment, Interest